The Types Of Illocutionary Found In The Main Character’s Utterances In Alladin Movie - Meilasari, Ni Luh Putu Nevik; Putri, I Gusti Ayu Vina Widiadnya (Institut Pariwisata dan Bisnis Internasional, 2025)
This study is concerned with analyzing the research entitled Illocutionary Acts Found In The Main Character’s Utterances. This research is concerned with identifying the types of illocutionary acts used by the main characters, how often the types of illocutionary acts occurred, and which types appeared most frequently in the movie. This research utilized qualitative method, which is the data were achieved by watch the movie. Five types of illocutionary acts were discovered in the utterance of the main characters in Alladin movie as a result of this analysis. Those are declarative, representative, expressive, directive, commissive. The qualitative method was applied to find out the frequency and the types of illocutionary acts used in alladin movie. The researcher found five types those are directive 3 data or 23%, expressive 3 data or 23% , representative 2 data or 15%, commissive 1 data or 8%, and declarative 4 data or 31% used in alladin movie. The most frequent type used was declarative. Keywords: illocutionary acts, main characters, movie